Study of the workplace accidents caused by human error in the manufacturing industry using structural equation modelling (SEM) - Natalee, Corbett (2022)
In the manufacturing industry, human error is an aspect that is a common occurrence. This can happen whether intentional or unintentional and may affect the flow of work in the plant depending on the severity of the error. The purpose of this study is to examine the relationship between safety knowledge, unsafe behaviour and workplace accidents to human error. The focus of this study is on the manufacturing industry in Malaysia. The total number of respondents that were sampled in this study was 117 respondents who were recruited by sending out Google Form surveys from various parts of the country. Based on the demographic profile of the respondents, most of the respondents are located in Penang and are working in large sized companies with the number of full-time employees being more than 200 in the electrical and electronics industry as Engineers. The survey results were then studied using SmartPLS in order to find out the correlation between safety knowledge, unsafe behaviour and workplace accidents to human error. Since the values of the loadings for each of the items are more than 0.5, with a range of 0.778 to 0.929, they are considered to be reliable. Other than that, the results show that there is a significant positive impact of unsafe behaviour to human error with the largest factor loading of 0.437. Besides that, since there are positive values for the values of the loadings between the independent and the dependent variables, that is more than 0, it can be concluded that there is a positive relationship between the Safety Knowledge, Unsafe Behaviour and Workplace Environment to Human Error. In conclusion, the factor loading of workplace environment to human error is 0.252 which also shows that there is a significant positive impact of workplace environment to human error. Lastly, safety knowledge also is found to have a significant positive impact on human error with a factor loading of 0.152. The results obtained from this study can be used in order to take into account and further explore the relevance of the relationship between these variables.